(3x +a) (bx-3)= 6x^2 +x-15
The equation is true for all values of x, when a and b are constant. What is the value of ab?
i did the foil method and came up with 10. Is that correct? or is it -10?
$\displaystyle \displaystyle \begin{align*} (3x + a)(b\,x - 3) &= 3b\,x^2 + (ab - 9)x - 3a \end{align*}$
For this to be equal to $\displaystyle \displaystyle \begin{align*} 6x^2 + x - 15 \end{align*}$ it requires that $\displaystyle \displaystyle \begin{align*} ab - 9 = 1 \end{align*}$, and so $\displaystyle \displaystyle \begin{align*} ab = 10 \end{align*}$ as you found.